(untitled) (Bangladesh Medical Journal Khulna, 2014)
Radiological examination, endoscopy, cytology, biopsy and detection of p21 oncogens and others have resulted in the identification of early cases of gastric carcinoma. Among these, endoscopic biopsy is an important tool to detect gastric carcinoma. But some times, it can not give information due to inadequate and improper sampling. On the other hand,modern diagnostic tools of detecting gastric carcinoma as like detection of p21 oncogens and others are not available in our country. So, In conjunction with imprint cytology, it is possible to reach an accurate diagnosis. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18239 Bang Med J (Khulna) 2013; 46 : 34-36